Effects of antifreeze proteins on cryopreserved sterlet (Acipenser ruthenus) sperm motility variables and fertilization capacity - Xin, Miaomiao; Tučková, Vladimíra; Rodina, Marek; Kholodnyy, Vitaliy; Dadras, Hadiseh; Boryshpolets, Sergii; Shaliutina-Kolešová, Anna; Linhart, Otomar (Animal reproduction science, 2018)
The effect of antifreeze proteins on sterlet, Acipenser ruthenus sperm motility variables and fertilization rate were investigated after cryopreservation. Two types of antifreeze proteins (AFPI or AFPIII) were used at concentrations of 0.1, 1, 10 and 100 μg/mL. The motility variables of fresh and cryopreserved sperm with and without addition of antifreeze proteins were evaluated by the Computer Assisted Semen Analyzer (CASA). The fertilization rate using about 200,000 spermatozoa per egg was evaluated after 54 h incubation at 17 °C during the early stage of organogenesis. The motility, curvilinear velocity and straight-line velocity of fresh sperm was 93 ± 5%, 128 ± 13 μm/s and 89 ± 9 μm/s, respectively. There was a significant decrease of sperm motility rate between fresh sperm and cryopreserved sperm with/without addition of antifreeze proteins. The greatest motility among thawed samples was in the sperm cryopreserved with 10 μg/mL of AFPI (56 ± 20%), however, these data were not different compared to the sperm without antifreeze proteins (49 ± 14%). No statistical variations were detected in curvilinear velocity nor straight-line velocity. The fertilization rate with fresh sperm was 67 ± 7%. No significant differences were detected in fertilization rate between fresh and cryopreserved spermatozoa with/without addition of antifreeze proteins, except the sperm cryopreserved with 100 μg/mL of AFPIII (39 ± 14%). Thus, it is concluded that addition of antifreeze proteins to cryopreservation medium do not improve nor have toxicity effects on the quality and fertilization capacity of sterlet sperm after thawing.
Keywords: Spermatozoa; Animals; Cryopreservation; kryoprezervace; Antifreeze Proteins; Fertilization; Semen Preservation; fertilizace; zvířata; mužské pohlaví; Fishes; Male; Sperm Motility; spermie; uchování spermatu; kryoprotektivní proteiny; motilita spermií; ryby